Does the Linder hypothesis hold? Recent Japanese case - Kurihara, Yutaka (Archives of Business Research, 2021)
The theory of comparative advantage has for a long time played one of the most important roles among the theories of international economics. The theory says that a country has to specialize in producing and exporting goods and services that the country can produce at lower opportunity cost than other goods and services. Achieving this, both countries can benefit. The Linder hypothesis focuses on internal demand in a country. It states that the pattern of export goods is determined by internal demand structure. This study empirically analyzes this Linder hypothesis for the recent case of Japan. The Gravity model can be used to obtain theory-consistent estimates of the Linder hypothesis. This model can estimate bilateral international trade on the basis of cross-section data. The results show that the Linder effect has been holding well. Also, FTA (Free Trade Agreement) has been having positive impacts on international trade.